Effectiveness of STEAM-Integrated Project-Based Learning to Improve Creative and Collaborative Thinking Skills of Elementary School Students - Muzaini, M. Choirul; Khoiriyah, Zulfatul; Khabib, M. Aliful; Kuncoro, Reno (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
This study aims to describe the effectiveness of STEAM-integrated project-based learning in improving elementary school students' creative thinking and collaboration skills. The subjects of this study were at Babarsari State Elementary School, Depok Subdistrict, Sleman Regency, consisting of 14 grade V (five) students, with a composition of 8 male students and 6 female students, selected through purposive sampling technique. The type of research used was Classroom Action Research. Data were collected through interviews, observations, and tests. Data analysis was conducted using qualitative and quantitative techniques. The results showed that applying project-based learning models integrated with STEAM improved students' creative and collaborative thinking skills and learning outcomes. Students' creative and collaborative thinking skills increased from 26% and 28% to 78% and 80%, showing an increase of 52%. In addition, the average completeness of student learning outcomes increased from 21% to 79%, with a specific increase in the social studies learning outcomes of grade V students by 58%. This research highlights the effectiveness of the STEAM approach in improving students' skills and learning outcomes.